Geometric knowledge in the elaboration of an artifact in a Ñuu Savi community - García, Javier García; Bernandino Silverio, Noé Bernandino (IE Revista de Investigación Educativa de la REDIECH, 2019)
The goal of this paper is to identify the existing geometric notions in the design and elaboration of güilile (an artifact of widespread use) in a Ñuu Savi community. This artifact is a working tool and, according to the Tee Savi villagers (Mixtecos) helps to optimize the work. The research is based on ethnomathematics, in particular, on the practices of measuring, designing and explaining. This is qualitative research and employs the ethnographic method to study the social unit (community Ñuu Savi) and relies on semi-structured interviews (videotaped) to three key informants to collect the data. On the other hand, the explanation of the results is descriptive and interpretative. The results indicate that in the design and elaboration of the güilile, the population of the Ñuu Savi community use diverse geometric notions such as circumference, the intersection of straight lines, parallel lines and paraboloid of revolution. From these results, some implications for teaching in the article are discussed.